Vaccination with SARS-CoV-2 inactivated vaccines reduced the risk of anxiety and depression in a population majored by health care workers during the recent omicron variant outbreak - Zhao, Hong; Yu, Xia; Ye, Wenyi; Wang, Runzhu; Sheng, Jifang; Shi, Yu (Frontiers in Psychology, 2022)
Background: Mental health status of the general population in China during the outbreak of Omicron virus variant strain after experienced the COVID-19 pandemic, and correlation between COVID-19 vaccine and mental health were not clear. Methods: A large-sample, cross-sectional, online survey study was conducted from April 12, 2022 to April 20, 2022. The prevalence of symptoms of depression, anxiety, and insomnia was evaluated using the hospital anxiety and Depression Scale, Ascension insomnia self-rating scale. Results: A total of 1387 participants provided informed consent and 55.9% reported symptoms of mental health. The incidence of anxiety (30.4% vs. 48,4%, p<0.001) and depression (27.1% vs. 46.3%, p < 0.001) were decreased with COVID-19 vaccine. On multivariate analysis, living Shanghai (anxiety: Odds ratio [OR]: 1.58, 95% confidence interval [CI]: 1.14-2.19, p = 0.006; depression: OR: 1.61, 95% CI: 1.16-2.25, p= 0.005), with mental illness (anxiety: OR: 8.97, 95% CI: 1.01-79.56, p = 0.049; depression: OR: 9.32, 95% CI: 1.06-82.30, p= 0.045) were increase the incidence of anxiety and depression. And elder participants (anxiety: OR: 0.986, 95% CI: 0.975-0.997, p= 0.012; depression: OR: 0.976, 95% CI: 0.965-0.987, p < 0.001), with COVID-19 vaccine (anxiety: OR: 0.49, 95% CI: 0.32-0.75, p= 0.001; depression: OR: 0.45, 95% CI: 0.29-0.69, p< 0.001) were decrease the incidence of anxiety and depression. Conclusions: The results of this survey indicate that mental health symptoms may have been common during the outbreak of Omicron variant strain even if experienced the COVID-19 pandemic, and vaccination may reduce the risk of anxiety and depression.